2016
DOI: 10.1074/jbc.m116.749408
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Activity in Human White Adipocytes Is Regulated by the Ubiquitin Carrier Protein 9/microRNA-30a Axis

Abstract: The acquisition of beige adipocyte features by white fat cells corresponds to protection against obesity-induced metabolic diseases in humans and animal models of type 2 diabetes. In adipose tissue, expression of the E2 small ubiquitin-like modifier ligase ubiquitin carrier protein 9 (Ubc9) is positively correlated with markers of insulin resistance and corresponds with impaired browning of human white adipocytes. However, the molecular regulation of Ubc9 expression in adipocytes and other cells remains unclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 48 publications
1
26
0
1
Order By: Relevance
“…For example, Ubc9 (ubiquitin carrier protein 9) expression is regulated by miR-30a in human subcutaneous adipocytes [34]. miR-30a reduces IRF4 expression through specific binding with the 3′UTR, thereby suppressing the Th17 differentiation and preventing the full autoimmune encephalomyelitis development [35].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Ubc9 (ubiquitin carrier protein 9) expression is regulated by miR-30a in human subcutaneous adipocytes [34]. miR-30a reduces IRF4 expression through specific binding with the 3′UTR, thereby suppressing the Th17 differentiation and preventing the full autoimmune encephalomyelitis development [35].…”
Section: Discussionmentioning
confidence: 99%
“…(128)(129)(130)(131)]. More recently, it was shown that miRNA30a controls Ubc9 levels in human subcutaneous adipocytes, with consequences for their mitochondrial activity (132). Another way to directly regulate the E2 catalytic activity is the previously-discussed transient disulfide bridge formed between the catalytic cysteines of the E1 and the E2 enzymes (94,95).…”
Section: E2 Regulationmentioning
confidence: 99%
“…For example, the expression of Ubc9 is regulated by miRNA-30a in human subcutaneous adipocytes [34]. miR-30a reduces IRF4 expression through the specific binding with the 3′ UTR, thus suppressing theTh17 differentiation and preventing the full development of autoimmune encephalomyelitis [35].…”
Section: Discussionmentioning
confidence: 99%